Embodying Theology: Trauma Theory, Climate Change, Pastoral and Practical Theology - McCarroll, Pamela R. (Religions, 2022)
Since 2009, the amount of literature focused on the psychological and social dimensions of the climate crisis has increased exponentially. This growing interest in the topic is signaled especially in the American Psychological Association (APA)’s multiple reports on the mental health impacts of climate change. More recently, across different disciplines, links have also been made between trauma theory and the climate crisis. These rich discussions include overlapping concerns, areas of potential fruitfulness and theological implications for all the practical theological disciplines, especially for pastoral theology and practices of care. Given the implicitly existential, theological and spiritual dimensions embedded in the realities of both trauma and the climate crisis, there is an important opportunity for pastoral theology in particular, and practical theology more generally, to engage, learn from and contribute to the interdisciplinary conversation. In this paper, I first offer a brief overview of the literature in pastoral theology related to the climate crisis. Second, I present literature specifically on trauma theory and the climate crisis, outlining several of the key themes emerging across the interdisciplinary discussion. Third, I reflect theologically on the presented content, discussing and drawing forward areas of theological, epistemological and practical fruitfulness for practical and pastoral theology.